Indications for chemoradiotherapy in older patients with locally advanced head and neck cancer in Japan: a questionnaire survey in the JCOG head and neck cancer study group - Koichi Yasuda; Naomi Kiyota; Kazuto Matsuura; Satoshi Saito; Yoshitaka Honma; Yoshinori Imamura; Kaoru Tanaka; Sadamoto Zenda; Takuma Onoe; Takeshi Kodaira; Satoshi Kobayashi; Hidefumi Aoyama; et al. (Frontiers in Oncology)
IntroductionChemoradiation therapy (CRT) with concurrent high-dose cisplatin (CDDP) is one of the standard treatment options for locally advanced head and neck cancer. Since the indications specific to the older population have not been reported, we conducted a multicenter survey on the indications.MethodsIn April and May 2023, a questionnaire survey was emailed to all institutions belonging to the JCOG-HNCSG, consisting of 37 institutions.ResultsThe major factors influencing the indications for high-dose CDDP were renal function and performance status (PS). The majority agreed that the treatment is administered to patients aged 65–74 years with PS 0–1 and 65–74 years with eGFR ≥60 (ml/ min/1.73m2), and not in patients aged ≥75 years with PS 2, ≥80 years with PS 1, and ≥65 years with eGFR <60. Regarding weekly CDDP, the majority agreed that the treatment is not conducted in patients aged ≥75 years with PS 2, ≥65 years with eGFR <40, and ≥70 years with eGFR <50.DiscussionIn Japan, where CRT is actively performed even among older people, a survey was conducted to determine its indications. Renal function and PS were considered important, and comorbidities, such as heart failure, were considered while determining the indication. These results will help define the eligibility criteria for prospective studies on CRT in older patients.